2007
DOI: 10.1016/j.jana.2006.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Consumer Voices: Planning HIV/Sexually Transmitted Infection Prevention in Alcohol Detoxification

Abstract: The literature has provided ample evidence that individuals abusing or dependent upon alcohol are at high risk for contracting HIV and other sexually transmitted infections (STIs). Despite the documented need of this vulnerable group for targeted HIV/STI prevention efforts, no prior research has explored the efficacy and feasibility of HIV/STI prevention for individuals in alcohol detoxification. The current study sought the voices of consumers of such services to get their guidance about successful and necess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…For example , Tracy et al (2009) surveyed SUD treatment clinicians regarding opinions and the delivery of services for STIs and found that clinicians were more likely to provide more of these services if they were more comfortable discussing sexual and intimate relationship issues. SUD treatment patients may respond better to HIV prevention interventions administered by counselors more comfortable with the material, in particular if counselors take a nonjudgmental stance (Brems and Dewane 2007).…”
Section: Implementation Of Hiv Prevention Interventions In Sud Treatmmentioning
confidence: 99%
“…For example , Tracy et al (2009) surveyed SUD treatment clinicians regarding opinions and the delivery of services for STIs and found that clinicians were more likely to provide more of these services if they were more comfortable discussing sexual and intimate relationship issues. SUD treatment patients may respond better to HIV prevention interventions administered by counselors more comfortable with the material, in particular if counselors take a nonjudgmental stance (Brems and Dewane 2007).…”
Section: Implementation Of Hiv Prevention Interventions In Sud Treatmmentioning
confidence: 99%
“…Individuals fear being labeled with HIV by their community just for being seen with that provider (Brems & Dewane, 2007;Roberts et al, 2001). Similarly, health care providers, writing about their experiences with rural patients in their local practices report that their patients in small communities experience greater stigma associated with HIV and that such stigma leads to harassment and discrimination (Verghese, Berk, & Sarubbi, 1989).…”
mentioning
confidence: 99%